The International Politics of Fashion: Being Fab in a Dangerous World - Madeleine Goubau (Communiquer)
Exploring how fashion can be a source of information and knowledge for the study of international relations is what Andreas Behnke proposes in his book “The International Politics of Fashion: Being Fab in a Dangerous World”. Throughout theoretical texts and case studies, the book highlights the fact that there is a need to study the intersection between fashion and international exchanges in a rigorous way and that the issues emerging from it are far from futile.